2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00779
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Reconstruct 3D Manhattan Wireframes From a Single Image

Abstract: In this paper, we propose a method to obtain a compact and accurate 3D wireframe representation from a single image by effectively exploiting global structural regularities. Our method trains a convolutional neural network to simultaneously detect salient junctions and straight lines, as well as predict their 3D depth and vanishing points. Compared with the state-of-the-art learning-based wireframe detection methods, our network is much simpler and more unified, leading to better 2D wireframe detection. With g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…For example, if a long line is broken into several short line segments, the resulted heat map is almost the same as the ground truth heat map, as shown in Figure 4. A good performance on the above two properties is vital for downstream tasks that rely on the correctness of line connectivity, such as inferring the 3D geometry through lines [24,36].…”
Section: Precision and Recall Of Line Heat Mapsmentioning
confidence: 99%
“…For example, if a long line is broken into several short line segments, the resulted heat map is almost the same as the ground truth heat map, as shown in Figure 4. A good performance on the above two properties is vital for downstream tasks that rely on the correctness of line connectivity, such as inferring the 3D geometry through lines [24,36].…”
Section: Precision and Recall Of Line Heat Mapsmentioning
confidence: 99%
“…Deep learning-based line segment detection methods has attracted great attention due to the remarkable performances [11,12,33,38,39]. AFM [32] presented regional partition maps and attraction field maps of line segment maps, followed by a squeeze module to generate line segments.…”
Section: Line Segment Detectionmentioning
confidence: 99%
“…We refer the interested reader to the recent study by Gryaditskaya et al [2019], who showed that a state-of-the-art deep network trained on synthetic drawings get confused by the many hidden and construction lines present in the sketches we target. The problem of parsing and reconstructing 3D wireframes has also been considered in computer vision, taking as input one or multiple photographs [Huang et al 2018;Usumezbas et al 2016;Zhou et al 2019], but these methods do not face the challenge of dealing with occlusion between lines since photographs only capture visible surfaces.…”
Section: Inputmentioning
confidence: 99%